Design, construction and commissioning of a packed bed reactor system for methane to methanol conversion - Guo, Junfeng (Department of Chemical Engineering, 2022)
The direct conversion of methane to methanol can have great economic implications and have been under extensive research for the past century. It is speculated that platinum-based catalysts may achieve this due to its ability to adsorb molecular oxygen as reactive surface oxygen species that may react with methane to form methanol. The selective conversion to methanol over such a catalyst might be possible through site blocking action with in presence of steam and/or high oxygen partial pressures as well as the presence of a promoter. Thus, a packed bed reactor system capable of safely operating under high pressures (< 50 bar) is designed and constructed to investigate the performance of platinum-based catalysts in the direct oxidative conversion of methane to methanol whilst co-feeding steam. The design procedure is carried out from flowsheet development to the detailed design of individual units of the reactor system. The constructed reactor system is built around a quartz lined microreactor 200 mm long and 2.4 mm in diameter to minimize risks associated with the flammability of methane and oxygen mixtures. A method for complete product analysis of all carbon containing reaction products using gas chromatography with flame ionization detector in conjunction with an oxidizer-methanizer microreactor is developed which is capable of quantifying minor carbon containing reaction products formed at low conversions with yields greater than 10 μmol/mol. Flow, pressure and temperature controls are also developed for the reactor system to ensure steady state operation.